Aspects of rural sindicalism in São Paulo - Ferrante, Vera Lúcia Silveira Botta (2009)
The paper tries to discuss aspects of the effect of rural sindicalism "leadership" in the State of São Paulo, meditating about the influence of sindicalism on the course of political acts and social movements in rural life.